FACELESS YOUTUBERS: HOW CONTENT CREATORS SHAPE AUDIENCE EXPECTATIONS - Dunham, Ian (AoIR Selected Papers of Internet Research, 2020)
YouTube's maturation as a platform can be seen through a collection of social norms, audience expectations, and politics, all of which weave themselves into the technosocial fabric of digital life. As such, certain practices that regulate the flow of information have become normalized across a certain subset of YouTube channels. This paper will look at this practice among YouTubers that are “faceless”—content creators who do not reveal their faces on camera while voluntarily revealing many other aspects of their identity. Specifically, a content analysis is performed on these channels: The Lockpicking Lawyer, AvE, SteadyCraftin, This Old Tony, bigclivedotcom, CGP Grey, and fastASMR. The wide range of categories these channels belong to (DIY, self help, science and technology, home crafting, electrical appliance teardown, and audio therapy) indicates that choosing to remain faceless is not a function of a certain type of material, but rather a salient trend that crosscuts YouTube genres. The channels analyzed suggest that these YouTubers feel empowered through remaining faceless, allowing for increased disclosure about the topic at hand. They also demonstrate that Faceless YouTubers selectively share information depending on a range of motivations, all of which revolve around imparting meaningful content to specific audiences while maintaining a specifically-constructed notion of privacy. As a platform that is continually evolving,this paper represents an advance in the study of YouTube.